2023
DOI: 10.3389/fonc.2023.1106434
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune microenvironment of cutaneous angiosarcoma with cancer testis antigens and the formation of tertiary lymphoid structures

Abstract: Cutaneous angiosarcoma (CAS) is a highly malignant tumor with few effective treatments. Although the indication for immune checkpoint inhibitors such as anti-PD-1 antibodies is expected to expand, there are many unknowns regarding the tumor immune microenvironment in CAS, which is generally considered an immunologically “cold” tumor. Our previous study demonstrated that tertiary lymphoid structures (TLSs) were associated with a favorable prognosis in CAS. However, we still don’t know what the difference is bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…The tumour immune microenvironment (TIME) plays a key role in identifying immune modifiers of cancer progression and developing cancer immunotherapies [37]. In addition, previous studies have indicated that upregulated or downregulated genes in different types of cancers can induce immune cells [38][39][40][41]. Several studies have indicated that the microenvironment plays important roles in immune escape and resistance to cancer treatments, leading to the progression of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The tumour immune microenvironment (TIME) plays a key role in identifying immune modifiers of cancer progression and developing cancer immunotherapies [37]. In addition, previous studies have indicated that upregulated or downregulated genes in different types of cancers can induce immune cells [38][39][40][41]. Several studies have indicated that the microenvironment plays important roles in immune escape and resistance to cancer treatments, leading to the progression of malignant tumours.…”
Section: Discussionmentioning
confidence: 99%